THE EFFECTIVINESS OF JIGSAW MODEL TO THE SOCIAL LEARNING RESULT FOR 4TH GRADE STUDENTS (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2017)
This research aimed to know: 1) the effectiveness of the jigsaw model toward the achievement of KKM social studies; 2) The great effectiveness of the jigsaw model on learning result; 3) The large increase in learning result with jigsaw model. This study uses a quasi-experimental design with shapes nonequivalent control group design. The sampling technique with cluster sampling. Data collected by the method of documentation and testing. Analysis of data using the proportion test, t-test, gain test and N-gain tes. The results showed: 1) results zhitung (1.743) ztabel (1.64), meaning that the jigsaw models effectively to the achievement of KKM social studies ; 2) results thitung (1.718) ttable (1.671), meaning the average result of learning jigsaw models larger than the STAD model; 3) the average gain of the experimental class, is 25.357 (medium category) and the average N-gain is 0.515 (medium category), it means a great learning result jigsaw model higher than STAD model. Based on these results, we can conclude that the model jigsaw is significantly more effective social studies.